Effectiveness of the Use of Mail Application Information Systems at the Center for Security and Enforcement of Environmental and Forestry Law in Sulawesi Region - Nawir Rahman; Andi Yusran Hasda; Risma Niswaty (International Journal of Administration and Education (IJAE), 2024)
Effectiveness of the Use of Mail Application Information Systems at the Sulawesi Region Environmental and Forestry Law Security and Enforcement Center (SIAP GAKKUM). The purpose of the study was to determine the Effectiveness of the Use of Mail Application Information Systems at the Sulawesi Region Environmental and Forestry Law Security and Enforcement Center (SIAP GAKKUM). The data collection techniques used are observation, interviews, and documentation. The informants in this study were the Head of the Administration Sub-Division, the Admin of the SIAP GAKKUM Application, Administration Staff, and 2 employees. The data analysis techniques used are data condensation techniques, data presentation, drawing conclusions or verification. The results showed that the management of letters at the Center for Security and Enforcement of Environmental and Forestry Law in Sulawesi Region, showed that the process of managing letters was in accordance with procedures so that it could be said to be effective. The use of cost and time is very efficient so that it can be categorized as effective, data security in the SIAP GAKKUM application can be guaranteed because access is only given to employees, application access and information can be accessed easily by employees according to the user account and account level owned. This research can be used as a reference material in the development of digital-based mail applications, there are several advantages of this application including efficient use of time, costs, data security guarantees, and flexible data access.